Characterization of gold mining waste for carbon sequestration and utilization as supplementary cementitious material - Syed Hasan, Sharifah Nur Munirah; Mohd Kusin, Faradiella; Nik Daud, Nik Norsyahariati; Saadon, Muhammad Anwar; Mohamat-Yusuff, Ferdaus; Ash’aari, Zulfa Hanan (Multidisciplinary Digital Publishing Institute, 2021)
This study aims to identify the potential of gold mining waste for CO2 sequestration and its utilization for carbon storage in cementitious material. Samples of mine waste were identified from a gold mine for mineralogical and chemical composition analysis using X-ray diffractogram and scanning electron microscopy with energy-dispersive X-ray. Mine waste was utilized in a brick-making process as supplementary cementitious material and as an agent for CO2 capture and storage in bricks. Carbonation curing was incorporated in brick fabrication to estimate CO2 uptake of the brick product. Results indicated that the mine wastes were composed of silicate minerals essential for mineral carbonation such as muscovite and illite (major) and chlorite-serpentine, aerinite, albite and stilpnomelane (moderate/minor phases). The mine wastes were identified as belonging to the highly pozzolanic category, which has a great role in improving the strength properties of brick products. Carbonated minerals served as an additional binder that increased the strength of the product. CO2 uptake of the product was between 0.24% and 0.57% for bricks containing 40–60% of gold mine waste, corresponding to 7.2–17.1 g CO2/brick. Greater performance in terms of compressive strength and water adsorption was observed for bricks with 3 h carbonation curing. The carbonation product was evidenced by strong peaks of calcite and reduced peaks for calcium hydroxide from XRD analysis and was supported by a densified and crystalline microstructure of materials. It has been demonstrated that gold mine waste is a potential feedstock for mineral carbonation, and its utilization for permanent carbon storage in brick making is in line with the concept of CCUS for environmental sustainability.